Health care professional perspectives on discharging hospitalized patients with injection drug use-associated infections. (October 2022) - Moore, Nichole; Kohut, Michael; Stoddard, Henry; Burris, Debra; Chessa, Frank; Sikka, Monica K.; Solomon, Daniel; Kershaw, Colleen M.; Eaton, Ellen; Hutchinson, Rebecca; Fairfield, Kathleen M.; Stopka, Thomas J.; et al.
Background: Patients with injection drug use (IDU)-associated infections traditionally experience prolonged hospitalizations, which often result in negative experiences and bad outcomes. Harm reduction approaches that value patient autonomy and shared decision-making regarding outpatient treatment options may improve outcomes. We sought to identify health care professionals (HCPs) perspectives on the barriers to offering four different options to hospitalized people who use drugs (PWUD): long-term hospitalization, oral antibiotics, long-acting antibiotics at an infusion center, and outpatient parenteral antibiotics. Methods: We recruited HCPs ( n = 19) from a single tertiary care center in Portland, Maine. We interviewed HCPs involved with discharge decision-making and other HCPs involved in the specialized care of PWUD. Semi-structured interviews elicited lead HCP values, preferences, and concerns about presenting outpatient antimicrobial treatment options to PWUD, while support HCPs provided contextual information. We used the iterative categorization approach to code and thematically analyze transcripts. Results: HCPs were willing to present outpatient treatment options for patients with IDU-associated infections, yet several factors contributed to reluctance. First, insufficient resources, such as transportation, may make these options impractical. However, HCPs may be unaware of existing community resources or viable treatment options. They also may believe the hospital protects patients, and that discharging patients into the community exposes them to structural harms. Some HCPs are concerned that patients with substance use disorder will not make 'good' decisions regarding outpatient antimicrobial options. Finally, there is uncertainty about how responsibility for offering outpatient treatment is shared across changing care teams. Conclusion: HCPs perceive many barriers to offering outpatient care for people with IDU-associated infections, but with appropriate interventions to address their concerns, may be open to considering more options. This study provides important insights and contextual information that can help inform specific harm reduction interventions aimed at improving care of people with IDU-associated infections.